Thinking clearly with data : a guide to quantitative reasoning and analysis - Bueno de Mesquita, Ethan, 1974-; Bueno de Mesquita, Ethan, 1974-; Fowler, Anthony (Princeton : Princeton University Press, 2021)
'This is an intro-level text that teaches how to think clearly and conceptually about quantitative information, emphasizing ideas over technicality and assuming no prior exposure to data analysis, statistics, or quantitative methods. The books four parts present the foundation for quantiative reasoning: correlation and causation; statistical relationships; causal phenomena; and incorporating quantitative information into decision making. Within these parts it covers the array of tools used by social scientists, including regression, inference, experiments, research design, and more, all by explaining the rationale and logic behind such tools rather than focusing only on the technical calculations used for each. New concepts are presented simply, with the help of copious examples, and the books leans towards graphic rather than mathematical representation of data, with any technical material included in appendices'--
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Sociology -- Statistical methods; Sociology -- Methodology